ROLE OF GLYCAEMIA LEVEL IN THE DEVELOPMENT OF INTERSTITIAL COLLAGEN IN PATIENTS WITH CORONARY HEART DISEASE AND TYPE 2 DIABETES - Rudenko, T. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
A role of blood glucose levels in the development of interstitial collagen has been studied in 84 patients (53 women and 31 men, average age 60 ± 2.4 years) with coronary heart disease (CHD). All patients were divided into twocomparable groups: a study group including patients with coronary heart disease andtype 2 diabetes mellitus (DM) and a control group consisting of patients with coronary heart disease without DM. All patients received standard medical therapy as recommended by the European Society of Cardiology. The level of blood glucose in both groups was assessed by the standard technique, a degree of interstitial collagen volume fraction (ICVF) was measured using the formula of J. Shirani et al. The data were processed by parametric and nonparametric statistical methods. It has been proved that hyperglycemia in type 2 diabetes contributes to the development of ICVF, the degree of which increases with the rise of blood glucose level. A high level ofICVF in patients with coronary heart disease and diabetes type 2 can be a predictor of myocardial dyssynchrony development and heart failure progression, therefore, a close monitoring and timely correction of changes of blood glucose levelsare recommended to prevent the complication development. ICVF evaluation should become a routine diagnostic method in all patients with type 2 diabetes.